CUSTOMER E-TRUST MEDIATION: THE ROLE OF E-SERVICE QUALITY AND LIVE STREAMING ON REPURCHASE BEHAVIOR IN THE SHOPEE MARKETPLACE - Anggrahadi, Daru; Haris, Helmi (UIN Raden Mas Said Surakarta, 2025)
This study aims to examine a research model expected to identify the effects of e-service quality and live streaming on consumer repurchase behavior on Shopee, with trust as a mediating variable. The respondent data were obtained from online questionnaires distributed to Shopee users and surveys administered to the people of Surakarta City, totaling 102 respondents over a three-month period from July to September 2025. This research employed SEM-PLS (Partial Least Squares) analysis using the SmartPLS 3 method. The analysis consisted of the outer model, inner model, and hypothesis testing. The hypothesis testing results indicate several positive and significant direct relationships, including: e-service quality has a positive and significant effect on purchases on Shopee; live streaming has a positive and significant effect on purchases on Shopee; e-service quality has a positive and significant effect on trust as a mediating variable; and live streaming has a positive and significant effect on trust as a mediating variable. However, trust does not have a positive and significant effect on consumer behavior. Regarding the mediation effect on consumer behavior, trust does not mediate the relationship between e-service quality and consumer purchasing behavior on Shopee, nor does it mediate the relationship between live streaming and consumer purchasing behavior on Shopee. This study is expected to provide beneficial theoretical implications as well as guidance for future research. In addition, the findings may serve as input for Shopee in designing trust-related programs that integrate e-service quality and live streaming